The Hanse in medieval and early modern Europe - Wubs-Mrozewicz, Justyna 1976-; Jenks, Stuart (The Northern world, 2013)
The Hanse in Medieval and Early Modern Europe discusses new research on this unique organization of towns and traders, and places the findings in the broader context of European economic, legal and social history.